Environmental Safety of Second and Third Generation Bioplastics in the Context of the Circular Economy - Garmulewicz, A (Academic Press, 2023)
Bioplastics derived from organic materials other than crude oil are often suggested as sustainable solutions for tackling end-of-life plastic waste, but little is known of their ecotoxicity to aquatic species. Here, we investigated the ecotoxicity of second and third generation bioplastics toward the freshwater zooplankton Daphnia magna. In acute toxicity tests (48 h), survival was impacted at high concentrations (g.L-1 range), within the range of salinity-induced toxicity. Macroalgae-derived bioplastic induced hormetic responses under chronic exposure (21 d). Most biological traits were enhanced from 0.06 to 0.25 g.L-1 (reproduction rate, body length, width, apical spine, protein concentration), while most of these traits returned to controls level at 0.5 g.L-1. Phenol-oxidase activity, indicative of immune function, was enhanced only at the lowest concentration (0.06 g.L-1). We hypothesise these suggested health benefits were due to assimilation of carbon derived from the macroalgae-based bioplastic as food. Polymer identity was confirmed by infra-red spectroscopy. Chemical analysis of each bioplastic revealed low metal abundance whilst non target exploration of organic compounds revealed trace amounts of phthalates and flame retardants. The macroalgae-bioplastic disintegrated completely in compost and biodegraded up to 86 % in aqueous medium. All bioplastics acidified the test medium. In conclusion, the tested bioplastics were classified as environmentally safe. Nonetheless, a reasonable end-of-life management of these safer-by-design materials is advised to ensure the absence of harmful effects at high concentrations, depending on the receiving environment. © 2023